Pengaruh Organizational Resilience, Job Satisfaction Terhadap Business Performance pada Perusahaan Pertamina. - Suciariani Suciariani (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2022)
Employees or workers in a company become one of the important assets for the company, therefore the company gives full concentration to the quality of the performance of its employees. This study provides information to human capital managers who play an important role in communication between teams so that they can establish a good relationship and can play an important role in providing direction or guidance to their employees in carrying out learning. Based on the results of the analysis of the influence of Organizational Resilience, Job Satisfaction, Organizational Learning Culture, and Turnover Intention on Business Performance, Pertamina companies can see the factors that influence employees in terms of the influence of Organizational Resilience, Job Satisfaction, Organizational Learning Culture, and Turnover Intention on Business Performance